(untitled) - Tremolet, Sophie (Washington DC, 2006)
Regulation is defined as a set of functions used to ensure that water and sanitation service (WSS) providers comply with existing rules on tariffs and quality and adapt those rules according to various circumstances. This note, financed by the Government of the Netherlands through the Bank-Netherlands Partnership Program (BNPP), provides practical guidance on how regulatory frameworks can be designed to expand access and improve WSS service to poor customers. To benefit the poor, regulatory frameworks must improve accessibility, affordability, and sustainability of these services. One of the best ways to do this is to provide poor customers with a reliable water supply through a piped network, for which clear coverage targets for operators must be defined. The regulatory framework must create competition so that a wide range of service options are available. It must also allow for differentiated service levels, give incentives to main operators to subcontract with smaller operators, and use incentives as well as obligations for operators to serve the poor. In addition, it must establish a tariff level that encourages greater access to services without jeopardizing financial stability. Whereas policy makers play the main role in establishing regulatory frameworks, the institutions in charge of carrying out regulatory functions such as ministries, asset-holding companies, customer groups, and NGOs, also have important roles to play.
Keywords: Water supply,Cung cấp nước; Accounting,Kế toán